2021
DOI: 10.3855/jidc.13674
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and social effects on the incidence of tuberculosis in three Brazilian municipalities and in Federal District

Abstract: Introduction: The territorial characteristics, heterogeneities of landscapes, and the regional profiles of Brazil show great disparities in the spatial distribution of tuberculosis burden. Objective of this study is to analyze the effects of environmental and social factors on tuberculosis incidence in three Brazilian municipalities and in the Federal District of Brazil. Methodology: We performed an ecological study carried out with 131,576 new cases of tuberculosis registered in the Brazilian national d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…19,20 Previous studies have identified other risk factors, including family history of infection, poor waste management and access to clean water. 21 Early observations in the Medan Tembung area showed an increase in the number of cases over the last 3 years. In 2020, 113 people were diagnosed with tuberculosis, and 215 new cases were identified in 2021.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Previous studies have identified other risk factors, including family history of infection, poor waste management and access to clean water. 21 Early observations in the Medan Tembung area showed an increase in the number of cases over the last 3 years. In 2020, 113 people were diagnosed with tuberculosis, and 215 new cases were identified in 2021.…”
Section: Introductionmentioning
confidence: 99%